(untitled) (Tanzania Medical Journal, 2025)
Background Fatty Liver Disease (FLD) is projected to be the leading cause of chronic liver disease among People living with HIV (PLHIV). Broad objective This study aimed at determining the magnitude and the associated factors for Fatty Liver Disease among People living with HIV attending Care and Treatment Clinic (CTC) at Temeke Regional Referral Hospital in Dar es Salaam, Tanzania. Methodology A hospital-based descriptive cross-sectional study was conducted between September and November 2020. Consenting adults aged ≥18 years and living with HIV, were enrolled in the study. A questionnaire with structured questions was used to collect socio-demographic, anthropometric measurements and clinical characteristics. Patients were fasted for a minimum of 8 hours before sonography and taking samples for lipid profile. Abdominal Ultra sonography (USS) was performed using B-mode and 3.5 MHz convex probe transducer (Dawei-DW 580, China, 2020) by a single trained investigator and confirmed by an experienced Radiologist; discrepancies were discussed by revisiting the images. FLD was defined as an increase in liver echogenicity compared to the right kidney. Independent predictors of FLD were analyzed using multivariate logistic regression; p value of < 0.05 was considered to be statistically significant. Results A total of 454 patients were enrolled into the study. FLD was visible from 118 (25.9%) (95% CI 22.0%-30.3%) patients. Factors significantly associated with FLD at multivariate analysis were; age group 40-60 years (aOR 1.74; 95% CI: 1.02 – 2.96 p=0.043), overweight (aOR 1.92; 95%CI: 1.05-3.51: p =0.034), obesity (aOR 3.46; 95% CI: 1.80 – 6.65: p < 0.001) and dyslipidemia (a OR: 2.63 95%CI: 1.58-4.39; p < 0.001). HIV viral load status and duration on combination antiretroviral therapy were not significantly associated with FLD. Conclusion and Recommendations One out of four PLHIV at Temeke Regional Referral Hospital CTC had Fatty liver Disease. Factors associated with FLD were age 40-60 years, overweight, obesity and dyslipidemia. We recommend weight reduction and regular screening for FLD among PLHIV with above risk factors.